1970
DOI: 10.14421/jpi.2013.22.419-440
|View full text |Cite
|
Sign up to set email alerts
|

Perspektif filosofis Sir Muhammad Iqbal tentang pendidikan Islam

Abstract: These are Sir Muhammad Iqbal's philophical views and his thoughts on Islamic education.This is a qualitative descriptive study that describes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…39 Through this pattern, the process of education will be born following the times, there is continuity, and refers to thoughts about humanity so that a dynamic and contextual Islamic education system emerges; 40 and will also give birth to insan kamil. 41 Education in Islam does not only include teaching and learning processes that transform mere knowledge. However, it also includes integral selfdevelopment to bring humans to their humanity perfection.…”
Section: Finding and Discussion Between Critical Pedagogy And Islamicmentioning
confidence: 99%
“…39 Through this pattern, the process of education will be born following the times, there is continuity, and refers to thoughts about humanity so that a dynamic and contextual Islamic education system emerges; 40 and will also give birth to insan kamil. 41 Education in Islam does not only include teaching and learning processes that transform mere knowledge. However, it also includes integral selfdevelopment to bring humans to their humanity perfection.…”
Section: Finding and Discussion Between Critical Pedagogy And Islamicmentioning
confidence: 99%
“…Muhammad Iqbal lahir di Sialkot, Punjab tepatnya pada tanggal 9 November 1877 (Lubis & Hitami, 2022;Muslim, 2557). Berbeda halnya dengan uraian yang dijelaskan Syarif Hidayatullah, tenaga pengajar Fakultas Filsafat Univesitas Gadjah Mada bahwa Muhammad Iqbal lahir pada tangga 22 Februari 1873 (Hidayatullah, 2013). Penulis dari beberapa referensi lebih setuju kepada pandangan pertama, bahwa Muhammad Iqbal lahir pada tahun 1877 M.…”
Section: A Riwayat Hidup Sir Muhammad Iqbalunclassified
“…Penting untuk diketahui, bahwa kota Sialkot merupakan salah satu kota peninggalan dari Dinasti Mughal India, dan ketika Iqbal lahir atau sebelum tahun 1947 M, masih termasuk wilayah India, dan sekarang sudah masuk menjadi wilayah Republik Islam Pakistan (Hidayatullah, 2013;Lubis & Hitami, 2022). Selain itu, letak kota Sialkot berada di perbatasan antara Punjab Barat dan Kashmir, dan disini terlihat bahwa nenek moyang Muhammad Iqbal berasal dari lembah Kashmir (Hendri, 2016).…”
Section: A Riwayat Hidup Sir Muhammad Iqbalunclassified
“…Even teachers treat students like their own children. Thus, it can be concluded that the implementation of the integration in the school, the house, and the community can be the basis for the creation of human beings (Hidayatullah, 2013;Saekan, 2017).…”
Section: The Integration Of Education Systems In School Home and Societymentioning
confidence: 99%